Other Things Being Equal - Wolf, Emma, 1865-1932 (Salt Lake City, UT : Project Gutenberg, 1999)
"Other Things Being Equal" by Emma Wolf is a novel set in the late 19th century that explores themes of family dynamics, societal expectations, and personal identity. The story centers around Ruth Levice, a young Jewish woman navigating her relationships with her parents and her friendships, while also dealing with the complexities of her mother's deteriorating health and her father's attempts to balance family life with societal obligations. At the start of the novel, we are introduced to Ruth as she engages in a seemingly casual conversation with her cousin Jennie about her mother's well-being. The opening scenes touch on various familial and social dynamics, revealing Ruth's innate sense of responsibility toward her mother and the contrasting perspectives she has with Jennie about the Jewish-Christian social interactions in San Francisco. The initial chapters set the stage for Ruth's personal growth as she grapples with her mother's illness, her father's protective nature, and her own evolving desires for independence and agency within society. (This is an automatically generated summary.)
Release date is 1999-08-01
Produced by Barbara Cantalupo, and David Widger
Keywords: Love stories; Domestic fiction; San Francisco (Calif.) -- Fiction; Jewish fiction; Jewish families -- Fiction; Jews -- California -- San Francisco -- Fiction; Interfaith marriage -- Fiction; Jewish women -- Fiction